Review of research publications on postdoctoral research fellowship: Implications for African institutions - Moyo, Z. (South African Journal of Higher Education, 2021)
The recent surge in global knowledge production has attracted focus on postdoctoral research fellowship in developed countries, leaving this group of African academics in the shadows. This article reported the results of a systematic review of research of postdoctoral research fellowship. The database of this review comprised 44 mixed sources located via a systematic method. The social justice theory was adopted to analyse and interpret the findings. The analysis of data relied on the use of descriptive statistics and graphing techniques. The review found literature published predominantly in European and Anglo-American societies, affirming the emerging status of the African society in the contribution to global knowledge production. Recommendations were made for funding research activities, curbing brain drain and increasing research output in Africa. The study highlighted milestones of progress along topics, methodologies and “blind spots” for future research practice and apprises evidence based decision making by policy makers.